Designing Aerosol Therapies Based on the Integrated Evaluation of In Vitro, In Vivo, and In Silico Data - Margaret Bourlon; Yu Feng; Lucila Garcia-Contreras (MDPI AG, 2023)
Despite the advantages of the pulmonary route of administration and inhalable dosage forms, other routes of administration and dosage forms are often considered first to treat lung diseases. This occurs, in part, due to the perceived limitations of inhaled therapies resulting from the improper design and interpretation of their in vitro and in vivo evaluation. The present study outlines the elements that should be considered in the design, performance, and interpretation of the results of the preclinical evaluation of novel inhaled therapies. These elements are illustrated using an optimized model poly(lactic-co-glycolic) acid (PLGA) microparticle (MP) formulation to optimize the site of MPs deposition. The different expressions of MP size were determined, and their aerosol performance in devices used for animal (Microsprayer® and Insufflator®) and human studies (nebulizer and DPIs) was assessed using inertial impaction. Radiolabeled MPs were delivered to the lungs of rats by spray instillation to determine their site of deposition using single-photon emission computed tomography (SPECT) imaging. Recommendations to optimize the in vitro determinations are given, as well as suggestions to evaluate and interpret in vivo data in the context of the anatomy and physiology of the animal model and the corresponding in vitro data. Recommendations for the proper selection of in vitro parameters to inform in silico modeling are also given, as well as their integration with in vivo data.